Malcolm Chapman (ed.): Social and Biological Aspects of Ethnicity - Veber, Hanne (Tidsskriftet Antropologi, 1994)
Malcolm Chapman (ed.): Social and Biological Aspects of Ethnicity Anmeldes af Hanne Veber